Pengolahan Barang Bekas menjadi Produk Fungsional Bernilai Estetik - Ela Suryani; Lisa Virdinarti Putra (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The dominance of the use of plastic bottles, glass bottles, and cans in various types of products has been increasingly consumed by the public. This has an impact on environmental pollution because inorganic waste that accumulates will take a long time to decompose naturally. Everyone should understand 3R from the beginning, namely reduse (reducing the use of materials that damage the environment), reuse (reuse), and recycle (recycling goods) according to Law No.18 of 2008 and PP No.81 of 2002 concerning waste management . Genuk 01 Elementary School students do not understand how to recycle recycled inorganic waste) into functional items that are esthetically valued at 71% while the amount of inorganic waste (plastic bottles, glass bottles, and cans produced by students in schools is 53%. The method used is the method of participation active through stages: 1) program socialization and material submission; 2) training; 3) utilization of results; and 4) monitoring and evaluation. The results of the implementation of the Genuk 01 Elementary School Education Program in Ungaran Barat District, Semarang Regency were able to increase the understanding of 3R by 21% (initially 71% to 91%); recycling ability increased by 35% (initially 59% to 94%); and the ability to produce functional products with aesthetic value increased 38% (initially 62% to 100%). A positive response from Grade IV students at SDN Genuk 01 in carrying out greening in front of the class by utilizing plant pots from used plastiik bottles which were the products of PkM.